Technology blueprint: Kytty litter box / Nik Nur Afriza Yunan…[et al.] - Yunan, Nik Nur Afriza; Amran, Syazlina Akmar; Anuar, Siti Mudzalifa; Husin, Nor Haslina; Zainal Abidin, Fathin Afifah (2020)
The product being produced by Kytty Sdn. Bhd. is the Kytty litter box. Kytty litter box is a removable box where it can be placed anywhere especially outdoors and it is attached to the dustbin. It is practical for the consumer whom has many pets such as dogs and cats at home. Nowadays, there are many types of litter box that beautifully designed. However, the traditional method of cleaning litter box is still by scooping it. It is dirty, hassle and time-consuming especially for owner of multiple cats. By designing this new Kytty litter box will help to solve those problems. The Kytty litter box is 47L x 39W x 33H cm which is large enough for big sized cats. This feature can provide the cats with privacy while retaining their litter inside the box. Basically, Kytty little box is made of two boxes. One is the complete box and another one will be cut in half and have holes around it. A wood/plastic pole will be used at top of the sifter to make it easier when sifting the litter. The top cover of the box can be removed for the cat that don’t want the place to be enclosed. Besides, two pieces of carbon filter used on the top of the box to remove odors. This feature can make it possible for people stay with the same room comfortably. This product also easy or simple to use. A hole was created in front of the litter box and lower sides will make it easy for the cats to enter and exit. The maximum height of the litter to be in the box is around 5 centimeters. Furthermore, this product also perfect for multi-cat-households. A hole is created in front of the box to make sure it is easy for the cat to come inside the box. The material used for Kytty is a sturdy plastic construction such as PVC board with a wide base for extra stability. The bin made of three layers with ability to be detect from the box manually. The first layer is the top. The second layer contains a hole shaped rectangle. The third layer contains semi-cylinder shape but also cut into half to put the plastic roll. At the top of the bin, there is a clipper to clip the plastic roll. The dimension of the bin is 30L x 39W x 33H cm